Common Clinical Presentation and Outcome of Severe Malaria in Pediatric Age Group (1-12 years) at Allama Iqbal Teaching Hospital, Dera Ghazi Khan, Pakistan: Common Clinical Presentation and Outcome of Severe Malaria in the Pediatric Age Group - Ilyas, Sonia; Ahmad, Muhammad Sarfraz; Leghari, Shakeel Ahmad; Akbar, Asma; Jabeen, Irum; Ullah, Asmat (Pakistan Journal of Health Sciences, 2025)
Malaria remains a significant public health challenge worldwide, particularly in tropical and subtropical regions. Objectives: To determine the clinical presentation and outcomes of severe malaria in children aged 1-12 years. Methods: This prospective observational study was conducted in the Pediatrics Department, Allama Iqbal Teaching Hospital, DG Khan, from May 2024 to January 2025, including children aged 1–12 years with severe malaria, selected via non-probability consecutive sampling. Demographic and clinical data were recorded at admission, and all patients received IV artesunate. Successful discharge was defined by full clinical recovery and stable vitals. Data analysis was done using SPSS version 26.0, employed chi-square/Fisher’s exact tests for categorical and t-tests for continuous variables, with p<0.05 considered significant. Results: In a total of 120 children, 80 (66.7%) were male. The median age was 7.0 (4.0-10.0) years. Malnutrition was identified in 59 (49.2%) children. Plasmodium vivax was the predominant malarial parasite identified in 84 (70.0%) children. The most common clinical presentations were severe anemia, impaired consciousness, seizures, and respiratory distress, observed in 82 (68.3%), 50 (41.7%), 30 (25.0%), and 22 (18.3%), respectively. Mortality was reported, and all children were successfully discharged. Significantly longer hospital stay was noted among children with seizures (8.0 [5.0-11.0] vs. 6.0 [4.0-8.0], p=0.024). Conclusions: Severe malaria in children most commonly presents with severe anemia, impaired consciousness, and seizures, with Plasmodium vivax as the predominant causative organism. All enrolled children recovered and were discharged without mortality, indicating favorable short-term outcomes under the current management protocol.